Women's collective action and its impact on their resilience in agri-food systems: a rapid evidence review - Booker, Francesca; Duffy, Janine; Nicolini, Giulia; Núñez del Prado Nieto, Isabela; Wagner, Kata; Verma, Benu; Anbacha, Abiyot; Puskur, Ranjitha; Kori, Pooja (CGIAR GENDER Impact Platform, 2025)
This rapid evidence review set out to explore the empirical evidence on how collective action among women has impacted their ability to cope with a shock or stress in the context of agri-food systems. The research question was: What are the differential impacts of women’s collective action on their resilience to climate, environmental, economic, health and/or political shocks and stressors in the context of agri-food systems in low-or middle-income countries? We conducted literature searches using Scopus, Google and organizational websites identifying 33 studies covering 27 low- or middle-income countries for inclusion in the review. The form of women’s collective action most covered in the evidence was related to saving groups and were in rural settings. Using thematic analysis, the authors detailed five groups of impact: (1) access to finance for food security and household costs; (2) access to finance to diversify and enhance livelihoods; (3) peer support and resource sharing; (4) knowledge and skills training; and (5) resilience of the collective action. We also conclude with five broad reflections: (1) challenges around defining and measuring resilience; (2) limits to the financial sustainability of women’s collective action; (3) questions about the longevity of knowledge transfer in women’s collective action; (4) limited insights on moderating factors; and (5) more investigation into the causal pathways through which collective action impacts on women’s resilience. We caution overinterpreting the findings that were based on few types of women’s collective action, scant detail on definitions and measures of resilience, and a bias to observational inquiry. We underline that a lack of intersectional inquiry undermines our ability to understand women beyond typical treatment in research as one homogenous group. A key priority is that future research must use an intersectional lens, exploring how factors like age, ethnicity, and socioeconomic status (as examples) influence access to and benefits from collective action and, in turn, create differential outcomes for women’s resilience.